2 The work of the British School at Athens, 2021–2022. (November 2022) - Bennet, John
Abstract : This article, based on an oral presentation in virtual format by the author at the British School at Athens (BSA) Annual General Meeting on 9 February 2022, summarizes the activities of the BSA with a focus on the calendar year 2021. It describes – selectively and concisely – research by award holders, BSA-sponsored fieldwork and study in 2021, research and events associated with the Fitch Laboratory and the Knossos Research Centre, plus other activities of the BSA in Greece and the UK, including seminars, conferences, and workshops.